2011
DOI: 10.1038/ejcn.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

Higher vitamin D intake is needed to achieve serum 25(OH)D levels greater than 50 nmol/l in Québec youth at high risk of obesity

Abstract: Background/Objectives: Vitamin D levels are often observed to be low in Canadian youth, despite the mandatory fortification of fluid milk. We identified modifiable correlates of plasma vitamin D concentrations to inform public health efforts to remediate low-vitamin D status. Subjects/Methods: We recruited 159 children aged 8-11 years, who were at at high risk of obesity, non-systematically during different seasons. Vitamin D status was assessed by measuring plasma 25-hydroxyvitamin D (25(OH)D) using a radioim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…This is likely due to the fact that intake of these nutrients did not significantly increase on the GFD and remained persistently low, a finding that is supported within the literature, particularly in Canada where intakes of vitamin D are generally low in healthy children and adolescents (El Hayek et al, 2010;Ohlund et al, 2010;Wild et al, 2010;Mark et al, 2011). Although a few children were taking a vitamin supplement (n ¼ 5), these were consumed on an ad hoc basis, and likely did not contribute sufficiently to overall vitamin D/calcium nutriture and bone health.…”
Section: Discussionmentioning
confidence: 64%
“…This is likely due to the fact that intake of these nutrients did not significantly increase on the GFD and remained persistently low, a finding that is supported within the literature, particularly in Canada where intakes of vitamin D are generally low in healthy children and adolescents (El Hayek et al, 2010;Ohlund et al, 2010;Wild et al, 2010;Mark et al, 2011). Although a few children were taking a vitamin supplement (n ¼ 5), these were consumed on an ad hoc basis, and likely did not contribute sufficiently to overall vitamin D/calcium nutriture and bone health.…”
Section: Discussionmentioning
confidence: 64%
“…Intakes of many nutrients were substantially lower than recommended intake levels in both groups. Most participants failed to meet the RDA of vitamin D. This is very similar to the general population of Canadian children [27,28] that indicates that suboptimal vitamin D intake in children with CD is not due to the GFD alone, but rather due to reduced intakes of vitamin D fortified dairy products in Canadian children [27][28][29][30]. Most children were only able to meet the RDA for vitamin D with daily vitamin D supplementation in the range of 600-1000 IU/D (predominantly in the form of a single vitamin preparation).…”
Section: Discussionmentioning
confidence: 77%
“…One study performed seasonal supplementation of 13,700 IU over seven days (TABLE 1). None of the studies reported side effects during supplementation (19)(20)(21)(22)(23)(24) . (24) 159 Canadian children of both sexes.…”
Section: Figure 2 Prevalence Of Vitamin D Deficiency Between Articlementioning
confidence: 99%
“…The reviewed articles differ in some respects such as the serum 25(OH)D values considered to be deficient, insufficient or adequate. Three of the six articles considered deficiency as levels below 20 ng/ mL (19)(20)(21) , one considered it as below 18 ng/mL (22) , another below 15 ng/mL (23) , and the latter below 11 ng/mL (24) . Therefore, half of the studies analyzed considered deficiency as below 20 ng/mL.…”
Section: Figure 1 Flowchart Review Of the Findings In The Databasementioning
confidence: 99%
See 1 more Smart Citation